The effect of enzyme induction on the metabolism of disopyramide in man. - Aitio, M L (1981)
1 The effects of rifampicin, phenytoin, and disopyramide treatments on the metabolism of disopyramide were studied in patients and volunteers. 2 Rifampicin treatment markedly increased the metabolism of disopyramide. 3 Phenytoin had effects similar to those of rifampicin. The effect subsided in 2 weeks after stopping the treatment. 4 The metabolism of disopyramide seemed fastest in the patient group with the higher dose of disopyramide. Both in patients and volunteers a significant increase occurred in the urinary mono-N-dealkyldisopyramide/disopyramide ratio during the first week of disopyramide therapy. This change can partly be due to pharmacokinetic differences between disopyramide and its metabolite. The inducing effect of disopyramide remained uncertain.